Advanced Materials Prepared via Metallic Reduction Reactions for Electrochemical Energy Storage. Issue 10 (2nd September 2020) - Zhang, Jiaming; He, Hanna; Tang, Yougen; Ji, Xiaobo; Wang, Haiyan
Abstract: Advanced materials with various micro‐/nanostructures have attracted plenty of attention in energy storage field over the past decades. Metallic reduction reactions (MRRs) possess the merits of low energy consumption, flexibility, convenience, and scalability, which have been considered as potential methods to acquire diverse micro‐/nanostructured materials. In this review, the latest progress of MRRs is systematically summed up, featuring the usage of metallic reductants (e.g., magnesium, aluminum, zinc, lithium) on synthesizing of advanced micro‐/nanostructured materials and their applications in various energy storage systems. The as‐obtained materials (e.g., carbon‐, silicon‐, germanium‐, antimony‐, and titanium‐based materials) can deliver various architectures, including solid spherical structures, hollow porous structures, core–shell structures, yolk–shell structures, core–satellite structures, and many kinds of 1D, 2D, 3D micro‐/nanostructures. Besides, the defect properties of materials can be well tuned via MRRs. The application progress of these materials as active electrodes, host materials, or functional interlayers for lithium ion batteries, lithium sulfur batteries, sodium ion batteries, or supercapacitors is reviewed. In the end, the strengths and insufficiencies of MRRs are discussed and the probable future research directions of MRRs are proposed. Abstract : Metallic reduction reactions (MRRs) possess great flexibility to design various micro‐/nanostructures of energy storage materials, which signally concern the electrochemical performance of energy storage devices. The latest progresses of MRRs, including structural design, micromorphology and applications, are summarized. Besides, the existing practical challenges and future prospects are also discussed.